Enriching Counseling Approaches With The Sufi Tradition And Moral Principles In The Digital Era - Syakur, Abd; Khoiroh, Muflikhatul (Jurusan Bimbingan dan Konseling Islam, 2024)
This article examines sufistic moral teachings as a basis for building an Islamic counseling model to overcome the negative impacts of the digital era such as addiction to online gambling, pornography, etc. This study is using qualitative model. The main data is about the doctrine and practice of sufism and Islamic moral principles; about the negative impact of social media which damages personality. Data is taken from books, journal articles, and scientific works using documentation technique. The collected data was analyzed using analytical-synthetic thinking technique. The result is; first, the digital era which makes life easier, turns out to have negative psychological-spiritual impact. For example, being apathetic, anti-social etc. Second, sufis are credited with providing a path to purity of heart, thereby making the soul healthy and happy. Their spiritual practices are appropriate to be an alternative in bulding Islamic counseling stategies. Primarily, to deal with mental health problems as a negative impact of social media. Among others are; 1) fa’ali counseling in the form of practicing righteous deeds which is based on Wahb bin Munabbih's spiritual practices. The aim is to eliminate laziness; 2) counseling for ‘grave pilgrimage’ which was built from Abdullah al-Imari's spiritual experience. The practice is; someone intends to visit a cemetery to meditate; make oneself aware (contemplate/tafakkur-tadhakkur), take lessons from the grave phenomenon; dhikr and pray to get the strength to fill life in the world with good deeds; 3) khauf and raja’ energy-based ascetic counseling based on Hasan al-Basriy's spiritual experience.